Genetic parameters and correlated responses in female reproductive traits in the GIFT strain - Hamzah, A.; Nguyen Hong Nguyen; Mekkawy, Wagdy; Hooi Ling Khaw; Hoong Yip Yee; Abu Bakar, Khairul Rizal; Ponzoni, R.W.; Mohd Nor, S.A. (Hindawi Limited, 2016)
The effect of selection for greater growth rate in the GIFT strain on traits related to female reproduction (weight at spawning, number of eggs, number of fry, total weight of fry and number of dead fry) was studied. Available records comprised 10 generations of data from a total of 935 breeding females with known pedigree. Female body weight at spawning was 255 g, whereas the averages for number of eggs, number of live fry at hatching, number of dead fry and total fry weight per spawning were 1444, 908, 64.90, and 7.24 g respectively. Heritabilities for reproductive traits were low to moderate (0.20 for number of eggs, 0.16 for number of hatched fry and 0.11 for fry weight per female at spawning). The genetic correlations between female body weight at spawning and reproductive traits were very low to low (0.01 to 0.31) and not significantly different from zero. The genetic correlations among reproductive traits (i.e. number of eggs, number of hatched fry and fry weight) were high (0.75 to 0.92). Phenotypic correlations were consistent with the genetic correlations, ranging from 0.56 to 0.85. Correlated responses in reproductive traits measured as differences in least squares means between Selection and Control lines were positive and significant (except for the number of dead fry) when age of females at spawning was fitted as a covariate. However, there were no significant differences in all studied traits when body weight of the female at spawning was fitted as a covariate within lines. This indicates that the greater reproductive rate was due to the greater size of females in the Selection line, but the efficiency of reproduction per unit weight of female did not change as a consequence of selection for growth.